2018
DOI: 10.1097/jom.0000000000001125
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Hearing Conservation Program Effectiveness

Abstract: Management commitment and counseling of workers about NIHL may be key factors in program effectiveness. A combination of qualitative and quantitative methods appears to be useful for assessing HCPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…In this scenario, these results agree with the study by Rabinowitz et al 16 , whose authors found a significant association between the HCP administrators' commitment and the program's effectiveness. They further highlighted that it is important that managers give priority and be committed to the implementation of preventive actions at the workplace, so the effectiveness of the HCP is not affected.…”
Section: 7% Partially Implementedsupporting
confidence: 92%
See 1 more Smart Citation
“…In this scenario, these results agree with the study by Rabinowitz et al 16 , whose authors found a significant association between the HCP administrators' commitment and the program's effectiveness. They further highlighted that it is important that managers give priority and be committed to the implementation of preventive actions at the workplace, so the effectiveness of the HCP is not affected.…”
Section: 7% Partially Implementedsupporting
confidence: 92%
“…In this regard, this seems to be a limitation of assessments that only consider the audiological results, which would possibly not be able to fully expound the effectiveness or quality of the HCP actions. The combined qualitative and quantitative assessments contribute to a more concise evaluation of the HCP quality and effectiveness 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…However, one of the participants in this study who is performing well in the hearing conservation program showed that hearing loss problems could be minimized if the hearing conservation program is adequately performed with constant attention expressed. It is essential to actively share and promote the experience of a workplace that has successfully implemented a hearing conservation program to other workplaces [11,18,19]. As one labor supervisor pointed out, sharing engineering control between workplaces can be strenuous in reality regarding intellectual property rights.…”
Section: Discussionmentioning
confidence: 99%
“…Including service members through focus groups or surveys will elicit feedback on issues such applicability of the content to their work and off-duty noise exposure, impacts of training on the mission, effectiveness in promoting hearing protection use, and usability of the learning platforms. Previous studies have shown focus groups to be a valuable tool in evaluating the effectiveness of hearing conservation programs (Rabinowitz et al, 2018) and has the opportunity to elicit feedback regarding experience with hearing protection. Focus groups will also be an opportunity to examine leadership engagement in promoting hearing conservation education programs since management involvement has been shown to impact the effectiveness of the programs (Rabinowitz et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown focus groups to be a valuable tool in evaluating the effectiveness of hearing conservation programs (Rabinowitz et al, 2018) and has the opportunity to elicit feedback regarding experience with hearing protection. Focus groups will also be an opportunity to examine leadership engagement in promoting hearing conservation education programs since management involvement has been shown to impact the effectiveness of the programs (Rabinowitz et al, 2018).…”
Section: Discussionmentioning
confidence: 99%